Accuracy of indirect method in detection of false intent - Ulatowska, Joanna (Legal and criminological psychology, 2018)
Purpose. Two studies were conducted to assess of the accuracy of an indirect method used to detect lies about past behaviour and intentions. Methods. In Experiment 1, participants (N = 123) assessed the veracity (direct condition) or cognitive effort (indirect condition) of interviewees who had planned or taken part in mock academic misconduct and then lied or told the truth about their intentions or past activities. In Experiment 2, 33 participants assessed the veracity of interviews on true and false intentions answering a direct question and three indirect questions. Results. As predicted, the indirect method was equally effective in detecting lies about past activities and intentions. The accuracy of this method was not reduced by asking direct and indirect questions together. Conclusions. The experiments provided further evidence that the indirect method of detecting deception is accurate and can also be used to detect lies about intent.